SUBCULTURE CAREER AS AN ALTERNATIVE TO JAPANOPHILIA OR WEEABOO (WIBU) YOGYAKARTA OTSURU COMMUNITY - Wardhana, Oky Wardhana (Commsphere: Jurnal Ilmu Komunikasi, 2023)
weeaboo. Wibu is synonymous with the word no life or the slang language is nolep. Negative stigma is attached to the person with the title of weather and is also often considered strange. Even though this weeboo is no different at all from individuals or other groups. Therefore, researchers are interested in researching this Wednesday using qualitative methods with interview, observation, and participation techniques as well as data triangulation. The results of this study indicate that, basically, weaboo are the same as other groups or individuals, but what makes them look bad in the public eye is the negative stigma attached to the word